Physiochemical Treatment of Wastewater Utilizing Polyaluminum Chloride for Khartoum North Wastewater Effluent (University of Khartoum Engineering Journal, 2022)
This paper focuses on the possibility of applying physiochemical treatment for industrial wastewater combined with domestic wastewater that are currently treated by the conventional activated sludge process in Khartoum North Treatment plant at Haj Yousif (Wad Dafeah). A lab-scale experiment was carried out utilizing Poly aluminum chloride (PAC) as a coagulant for determining the optimum dose to reduce the turbidity of the wastewater sample to the lowest level. The results of the lab-scale model showed that a dose of 0.8 ml/l of the PAC achieved significant removal of turbidity (from turbidity >1000 NTU of raw sewage to turbidity level of 18 NTU of the treated effluent). This dose of 0.8ml/l obtained from the lab-scale experiment was applied in a pilot plant of capacity 30 m3/d erected at the site of the treatment plant (Wad Dafeah). The process units utilized in the pilot plant were of minimum or negligible electrical power consumption. They include an inverted hydro cyclone for flash mixing of the coagulant, pipes arrangement to achieve hydraulic gentle mixing as flocculation process, vertical sedimentation tank to enhance efficient settling of particles and tertiary treatment using a rapid sand filter. Raw sewage of BOD5 = 5000 mg/l was introduced into the pilot plant and excellent quality of treated effluent was obtained. Removal efficiencies of both BOD5 and SS were high (97 % & 98% respectively).Treated effluent had BOD5 = 23 mg/l & SS = 22 mg/l. The high dose of PAC utilized for the treatment (0.8 ml/l= 1040 mg/l) can be reduced significantly if raw wastewater of lower BOD content such as domestic wastewater is treated. In a parallel study with the domestic sewage of BOD5 =350 mg/l, the PAC dose required was 0.1 ml/l (130 mg/l). Recycling of residual PAC in the sludge is recommended to decrease the cost of treatment. The approach & methodology followed in this study can be further adopted using other coagulant material such as ferric salts or other similar local product which can achieve high efficiency in reducing the load of organic substances in the wastewater with minimum cost.Keywords: Physiochemical; Poly aluminum chloride; inverted hydro cyclone